Being Indigenous in an Unlikely Place: Self-Determination in the Yakut Autonomous Soviet Socialist Republic (1920-1991) - Sidorova, Evgeniia; Rice, Roberta (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2020)
How and why is Indigeneity expressed differently in different contexts? This article examines the articulation and expression of Indigenous Rights in one of the most challenging contexts—that of Siberia in the Soviet Union era. Based on primary, archival research carried out in the Republic of Sakha, Russia, the review finds that re-claiming and re-defining Indigeneity can serve as the first step in crafting an effective challenge to the domination and control exercised by states over Indigenous populations. The study of Indigeneity in unlikely places has important ramifications for Indigenous Peoples worldwide who are struggling against colonial-minded governments that have not only deprived Indigenous Peoples of their lands and resources, but also suppressed their right to self-identification through imposed administrative definitions of Indigeneity.